PENGARUH EFEKTIVITAS APLIKASI SISTEM INFORMASI DAN PELATIHAN TERHADAP KINERJA ADMINISTRATOR DI LINGKUNGAN BALAI PENDIDIKAN DAN PELATIHAN KEAGAMAAN MEDAN - Anthony Hardinal Sijabat; Rizkia Daulay (Jurnal Analisa Pemikiran Insan Cendikia (Jurnal APIC), 2022)
In order to optimize efficient, transparent and effective public service, information technology has a significant role in accomplishing the e-Government. Medan Religious Education and Training Center in one of the third echelon unit in Ministry of Religious Affairs which has the task of providing technical and administrative services to all elements within the Agency of Research, Development, Education and Training. In accomplishing the task, one of the functions is to carry out the management of information system in Medan Religious Education and Training Center. This study was conducted to analyze the impact of the using of education and training information systems toward the performance of education and training in the Ministry of Religious Affairs of North Sumatera. This research was conducted using a survey method by applying the primer data obtained through the questionnaire. The population in this study is the administrator of SIMDIKLAT (The Information Systems’ Management of Education and Training). The number of samples taken in this study were 35 people. The data analysis technique used validity test, reliability test, classical assumption and multiple regression test, F Test, T Test, and coefficient of determination test. The results of this study indicate that: effectiveness gives a positive and significant impact toward the performance at alpha 5%.